Effect of temperature and time on the thanatomicrobiome of the cecum, ileum, kidney, and lung of domestic rabbits. (March 2019) - Lawrence, Kelsey E.; Lam, Khiem C.; Morgun, Andrey; Shulzhenko, Natalia; Löhr, Christiane V.
Knowledge of changes in the composition of microbial communities (microbiota) in tissues after death, over time, is critical to correctly interpret results of microbiologic testing from postmortem examinations. Limited information is available about postmortem changes of the microbiota and the associated microbial genes (microbiome) of internal organs in any species. We examined the effect of time and ambient temperature on the postmortem microbiome (thanatomicrobiome) of tissues typically sampled for microbiologic testing during autopsies. Twenty rabbits were euthanized and their bodies stored at 4°C or 20°C for 6 or 48 h. Ileum, cecum, kidney, and lung tissue were sampled. Bacterial DNA abundance was determined by RT-qPCR. Microbiome diversity was determined by 16S rRNA gene sequencing. By relative abundance of the microbiome composition, intestinal tissues were clearly separated from lungs and kidneys, which were similar to each other, over all times and temperatures. Only cecal thanatomicrobiomes had consistently high concentrations and consistent composition in all conditions. In lungs and kidneys, but not intestine, proteobacteria were highly abundant at specific times and temperatures. Thanatomicrobiome variation was not explained by minor subclinical lesions identified upon microscopic examination of tissues. Bacterial communities typically found in the intestine were not identified at extra-intestinal sites in the first 48 h at 4°C and only in small amounts at 20°C. However, changes in tissue-specific microbiomes during the postmortem interval should be considered when interpreting results of microbiologic testing.